2016
DOI: 10.1016/j.physbeh.2015.11.025
|View full text |Cite
|
Sign up to set email alerts
|

The effect of large milk meals on digestive physiology and behaviour in dairy calves

Abstract: It is commonly believed that young calves should not be fed more than about 2l of milk per meal. If calves are fed beyond this volume, it is said that the capacity of the abomasum may be exceeded and that milk could enter the rumen. This can disturb the microbial flora/fauna of the rumen and increase the risk of indigestion, diarrhoea and reduced growth. The aim of this study was to examine the effect of large milk meals on digestive physiology and behaviour in dairy calves. Six calves (19-23days of age at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 21 publications
3
36
2
Order By: Relevance
“…Recent studies in milk-fed calves have indicated that the abomasum of 3-week old calves increases in size during milk feeding and can manage a milk portion greater than 2–3 liters [55]. In addition, automated milk feeding facilitates the division of the daily milk ration into several portions, and calves provided milk ad libitum drink their daily ration in approximately 6 portions [10].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in milk-fed calves have indicated that the abomasum of 3-week old calves increases in size during milk feeding and can manage a milk portion greater than 2–3 liters [55]. In addition, automated milk feeding facilitates the division of the daily milk ration into several portions, and calves provided milk ad libitum drink their daily ration in approximately 6 portions [10].…”
Section: Discussionmentioning
confidence: 99%
“…Berends et al (2015) reported MR flowing to the rumen of nipple-fed veal calves given solid feed (measured using cobalt recovery) averaged about 20% of a meal. However, other researchers have reported even with meal sizes as large as 6.8 L, nipple-fed calves offered whole milk did not experience any liquid feed entering the rumen (Ellingsen et al, 2016). Despite conflicting evidence, it is reasonable to assume that some calves may experience liquid feed entering the rumen and therefore have exposure of the rumen microbiome to orally administered antibiotics on a regular basis.…”
Section: Effects Of Antibiotics In Milk Replacer On Performance and Dmentioning
confidence: 97%
“…Assume that b 1 calf on the second design level calculated by the RSP procedure to receive intervention B 1 , b 2 to receive dose B 2 , b 3 to receive dose B 3 , b 4 to receive dose B 4 , and b 5 to receive dose B 5 . The milk temperature to be used on the third design level for the seven new calves will then be allocated by weighted complete randomization (b 1 ,b 2 ,b 3 ,b 4 ,b 5 ) following the same procedure as explained for the second design level.…”
Section: Randomized Between-patient Rsp Designmentioning
confidence: 99%
“…For RSP, the three temperature outcomes a 1-3 in design level 1 indicates at the next dose k-factor-adjusted temperature A 1-3 to undergo randomization and they are selected to pinpoint the respective five temperatures clinically used in design level 2. Similarly, the three temperature-adjusted A 1-3 for small and large teats, respectively, give rise to the five next temperatures which in turn in design level 2 produce the clinical outcomes b [1][2][3][4][5] . Furthermore, the five temperature outcomes in design level 2 will undergo randomization and in turn point out the selected pathway for the seven next temperatures to be used in design level 3.…”
Section: Uncertainmentioning
confidence: 99%
See 1 more Smart Citation